A Moisture‐Driven Actuator Based on Polydopamine‐Modified MXene/Bacterial Cellulose Nanofiber Composite Film. (23rd April 2021) - Yang, Luyu; Cui, Jian; Zhang, Lei; Xu, Xuran; Chen, Xiao; Sun, Dongping
Abstract: As a new 2D material, MXene (Ti3 C2 T x ) shows great potential as a smart multifunctional humidity‐responsive actuator due to its high hydrophilicity and conductivity but suffers from ambient oxidation and mechanical brittleness. Inspired by the mussels, the authors overcome these weaknesses by designing and fabricating a nacre‐like and lamellar‐structured composite film that consists of polydopamine‐modified MXene and bacterial cellulose nanofibers, which shows improved properties as a moisture‐driven actuator. The actuator has high conductivity (2848 S cm –1 ), excellent tensile strength (406 MPa), and toughness (15.3 MJ m –3 ). Moreover, the actuator is highly sensitive to moisture with the advantages of fast response (1.6 s), large deformation (176°), and high actuation force output (6.5 N m –2 ). It is additionally demonstrated that the actuator works as the electrical switch, robotic arm, and motor in a moisture‐driven manner. Overall, it is believed that this work improves the drawbacks of current MXene‐based actuators, laying the groundwork for their wider applications as moisture‐driven devices. Abstract : Inspired by mussels and pearl‐like layered structures, a MXene‐based composite film with a "brick‐rebar" structure is designed simply by vacuum‐assisted filtration. The moisture‐driven actuator prepared based on the film has high mechanical performance, high conductivity, and excellent actuation performance. This work broadens the applications of MXene‐based smart actuators.